INTEGRATION OF FULL-TIME AND DISTANCE LEARNING IN PEDAGOGICAL POSTGRADUATE TRAINING SYSTEM - O.O. Sokurenko (Kherson State University, 2010)
The article deals with advantages and disadvantages of distance learning. The author analyses the features of elementary school teacher's training in the system of postgraduate teacher's training regarding full-time and distance learning.